Effect of mitoxantrone on DNA polymerase of Ehrlich ascites carcinoma cells - Xian Li-Jian; Li Han-Xi; Liu Zong-Chao; Pan Qi-Chao (Acta Pharmacologica Sinica; Vol 19, No 4 (July 1998): Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of mitoxantrone (Mit) on DNA polymerases of tumor cells. METHODS: DNA polymerases of Ehrlich ascites carcinoma cells were isolated by phosphocellulose column chromatography. The effects of Mit on DNA polymerase alpha, beta, and gamma were detected by method of K Ono. RESULTS: Mit inhibited DNA polymerase alpha, beta, and gamma, IC50 values were 11.9, 6.5, and 11.9 mumol.L-1, and Ki 1.86, 2.22, and 2.05 mumol.L-1, respectively. The inhibitory mode of Mit on DNA polymerase alpha, beta, and gamma was competitive. CONCLUSION: Mit is a strong inhibitor on DNA polymerase alpha, beta, and gamma. The inhibitory mode was competition with respect to template DNA.